Nutrition Profiles of American Women in the Third Trimester - Gennaro, Susan (2011)
PURPOSE: To develop a profile of common nutritional patterns among pregnant, African American women that will assist providers in identifying areas for improvement and change. STUDY DESIGN: This study was part of a larger NIH funded (R03NR008548-01) study that examined risk factors associated with preterm labor and birth in high risk and low risk African American women. Data were collected on high risk mothers (women experiencing preterm labor) prior to 34 weeks gestation and every four weeks until delivery. Data were collected on the low risk mothers beginning at 28 weeks and then every four weeks until delivery. For this study high risk and low risk groups were collapsed to examine food choices over time in all participants (n=58). METHODS: Nutrition intake was examined by conducting one 24 hour diet recall at each time point. Food models and portion size pictures were used to improve accuracy. RESULTS: Overall, dietary intake was suboptimal and micro and macronutrient intake during the third trimester did not vary. Energy (caloric) intake was inadequate with the time averaged probability of having inadequate caloric intake 64.4%. Protein intake was the most likely nutritional factor to be inadequate with a time averaged estimated probability of inadequate intake 25.1%. Micronutrient intake from food was also inadequate. CLINICAL IMPLICATIONS: The persistence of sub-optimal nutritional intake during the third trimester supports the importance of continually assessing nutritional status throughout pregnancy, with a focus on caloric requirements and protein intake.